Mowing for Money: A Dollar Sense Guide to Lawn Care Business Record Book - Kathleen C. Ruppert; Arlene Zavocki Stewart; Brian Owens; Robert Degner (EDIS)
Produced jointly by the Department of Environmental Horticulture and the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, ©1997.